2018
DOI: 10.1073/pnas.1811624115
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily conserved Tbx5Wnt2/2b pathway orchestrates cardiopulmonary development

Abstract: Codevelopment of the lungs and heart underlies key evolutionary innovations in the transition to terrestrial life. Cardiac specializations that support pulmonary circulation, including the atrial septum, are generated by second heart field (SHF) cardiopulmonary progenitors (CPPs). It has been presumed that transcription factors required in the SHF for cardiac septation, e.g., Tbx5, directly drive a cardiac morphogenesis gene-regulatory network. Here, we report instead that TBX5 directly drives Wnt ligands to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
105
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(119 citation statements)
references
References 90 publications
(159 reference statements)
9
105
1
Order By: Relevance
“…It has been observed that the DMP is not as developed and the mesenchymal cap is very diminutive. [216][217][218][219] Genes involved in the tool kit acting in normal and, when corrupt, in abnormal development include Tbx5, 72 PDGFRα, 171,218 and Sonic hedgehog. 216 It is interesting to note that disturbance of podoplanin can also lead to abnormal pulmonary vein connections, which normally are guided to the left atrium by the DMP.…”
Section: Malformations At the Inflow Tract Of The Heartmentioning
confidence: 99%
“…It has been observed that the DMP is not as developed and the mesenchymal cap is very diminutive. [216][217][218][219] Genes involved in the tool kit acting in normal and, when corrupt, in abnormal development include Tbx5, 72 PDGFRα, 171,218 and Sonic hedgehog. 216 It is interesting to note that disturbance of podoplanin can also lead to abnormal pulmonary vein connections, which normally are guided to the left atrium by the DMP.…”
Section: Malformations At the Inflow Tract Of The Heartmentioning
confidence: 99%
“…In the amphibian heart, the sinus venosus moves more anteriorly, and the pulmonary vein connects with the atrium through the dorsal mesocardium (Romer, 1971). The atrial septum is present in vertebrates with pulmonary respiration including lungfishes, amphibians, and amniotes (Lewis & Hanken, 2017;Moorman & Christoffels, 2003;Steimle et al, 2018). The atrial septum is present in vertebrates with pulmonary respiration including lungfishes, amphibians, and amniotes (Lewis & Hanken, 2017;Moorman & Christoffels, 2003;Steimle et al, 2018).…”
Section: Ra Signaling In Coronary Vessel Maturationmentioning
confidence: 99%
“…The orifice of the pulmonary vein is demarcated by DMP, part of the atrial septum originating from the posterior SHF; therefore, the pulmonary vein drains into the left side of the atrium (Tasaka et al, 1996). The atrial septum is present in vertebrates with pulmonary respiration including lungfishes, amphibians, and amniotes (Lewis & Hanken, 2017;Moorman & Christoffels, 2003;Steimle et al, 2018).…”
Section: Ra Signaling In Coronary Vessel Maturationmentioning
confidence: 99%
See 2 more Smart Citations